2011
DOI: 10.1007/s11192-011-0493-8
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration structures in Slovenian scientific communities

Abstract: We combine two seemingly distinct perspectives regarding the modeling of network dynamics. One perspective is found in the work of physicists and mathematicians who formally introduced the small world model and the mechanism of preferential attachment. The other perspective is sociological and focuses on the process of cumulative advantage and considers the agency of individual actors in a network. We test hypotheses, based on work drawn from these perspectives, regarding the structure and dynamics of scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 26 publications
6
67
0
2
Order By: Relevance
“…Studies focusing on specific scientific communities at country level, such as Italian academic economists (Maggioni and Uberti, 2011) and Slovenian scientists belonging to Physics, Biotechnology, Mathematics and Sociology (Kronegger et al, 2012), show evidence of small-world structure. In addition, for Slovenian scientists, some features of preferential attachment principle have only been confirmed for Mathematics and Sociology.…”
Section: Co-authorship Network and Patterns Of Collaboration In Sciementioning
confidence: 99%
“…Studies focusing on specific scientific communities at country level, such as Italian academic economists (Maggioni and Uberti, 2011) and Slovenian scientists belonging to Physics, Biotechnology, Mathematics and Sociology (Kronegger et al, 2012), show evidence of small-world structure. In addition, for Slovenian scientists, some features of preferential attachment principle have only been confirmed for Mathematics and Sociology.…”
Section: Co-authorship Network and Patterns Of Collaboration In Sciementioning
confidence: 99%
“…For example, several studies have used bibliographic data from online databases to examine the structures, dynamics, and evolution of research collaboration networks across disciplines Kronegger et al 2012Kronegger et al , 2015Mali et al 2012). While bibliometric analysis is demonstrably useful and important for understanding collaboration, such measures are not always able to capture the full range of social dynamics experienced in research collaboration.…”
mentioning
confidence: 99%
“…We can see that if the border between high and low is set to 0.2, the clustering into four groups is quite balanced. Also, there is no obvious pattern for belonging to a group related to soft/hard, lab/office (Kronegger et al 2012), or natural/technical science subfields types. Evolution of interdisciplinarity Evolution of interdisciplinarity observed by Mali et al (2010) showed that the amount of coauthored publications in the field of sociology increased over the last two decades (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005).…”
Section: Comparison Of Results Based On Project and Publication Collamentioning
confidence: 99%